Metaverse And Hajj: The Meaning Of Muslims In Indonesia - Fernando, Henky; Larasati, Yuniar Galuh (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2022)
This study describes and explains the meaning of Muslims in Indonesia in the discourse of the pilgrimage through the metaverse space. The description in this study will provide a more comprehensive discussion of the discourse of the pilgrimage through metaverse in the meaning of Muslims in Indonesia. This study uses a virtual ethnographic method, which emphasizes data collection through reading online news texts through the Google search engine using the search keyword “Wacana Ibadah Haji melalui Metaverse". The findings in this study show that the discourse of the pilgrimage through metaverse space such as visualization of Hajj symbols and imitation of Hajj practices through virtual reality (VR) methods, such as visualization of the Kaaba and the Grand Mosque. The two forms have significantly influenced the meaning of Muslims in Indonesia in evaluating the discourse of the pilgrimage through the metaverse space. This evaluation was shown by several religious organizations in Indonesia, such as the Indonesian Ulama Council, Nahdlatul Ulama, and Muhammadiyah.